Flypaper Effect in the Allocation of Regional Expenditure in Regency/City in West Sumatra Province - Mendra, Haris; Handra, Hefrizal; Yonnedi, Efa (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This study aims to analyze the effect of fiscal transfers (DAU, DAK, DBH) on local government expenditure in West Sumatra Province, focusing on the Flypaper Effect phenomenon, where local expenditure is more influenced by transfer funds from the central government than by Regional Original Revenue (PAD). The data used in this study includes information on local expenditure, PAD, as well as various types of transfer funds such as the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) for districts / cities in West Sumatra Province in the period 2019-2022. The method used in this study is panel data regression analysis to examine the relationship between fiscal transfer variables and regional expenditure. The results showed that regional expenditure in West Sumatra Province was more influenced by fiscal transfers than by PAD. This confirms the Flypaper Effect phenomenon, where grants from the central government are more likely to be spent than locally generated revenues. The implications of these findings suggest the need for policies to increase PAD and reduce dependence on fiscal transfers in order to create regional fiscal independence.